Effects of Plant Growth Regulators, Nitrogen Fertilization, and Irrigation on Eldarica Pine Seedlings - Darwiche, Amal O. (Arizona-Nevada Academy of Science, 1990)
From the Proceedings of the 1990 Meetings of the Arizona Section - American Water Resources Association and the Hydrology Section - Arizona-Nevada Academy of Science - April 21, 1990, Arizona State University, Tempe, Arizona === Effects of applications of cytokinin-like and gibberellic growth regulators, nitrogen fertilizer, and irrigation on the development of containerized eldarica pine (Pinus brutia var. eldarica) seedlings was studied in a greenhouse for 13 weeks. All concentrations of growth regulators reduced nitrogen content of needles and dry weight of shoots; importantly, medium and high concentrations also adversely affected root collar diameter growth and shoot elongation. Nitrogen fertilization alone was not significant in its effect on seedling development, due probably to the nitrogen-rich nature of the potting medium. It is suggested that contentration is a critical factor when applying growth regulators, as phytotoxicity of seedlings can result at high rates.